Author Topic: problem 4 (25)  (Read 1146 times)

Zhiman Tang

  • Jr. Member
  • **
  • Posts: 6
  • Karma: 0
    • View Profile
problem 4 (25)
« on: January 18, 2019, 07:01:19 PM »
uxy = uxuy
I use the hint and divide both sides by ux. I get ux = eu * f(x). I am stuck there. Could anybody help me out?

Wanying Zhang

  • Full Member
  • ***
  • Posts: 21
  • Karma: 6
    • View Profile
Re: problem 4 (25)
« Reply #1 on: January 18, 2019, 08:04:40 PM »
I would start from the beginning.
$$\frac{u_{xy}}{u_x} = \frac{u_x u_y}{u_x} \Rightarrow \frac{u_{xy}}{u_x} = u_y$$
Integrate both sides,
$$\ln{u_x} = u + f(x)$$
$$u_x = e^{u+f(x)} = e^u \cdot g(x)$$
$$\frac{\partial u}{\partial x} = g(x)e^u$$
$$\frac{\partial u}{e^u} = g(x)\partial x$$
Integrate both sides,
$$-e^{-u} = G(x) + h(y)$$
$$u(x,y) = -\ln (-G(x) - h(y))$$
OK. V.I.
« Last Edit: January 18, 2019, 09:04:29 PM by Victor Ivrii »